Pengaruh Beban Kendaraan Terhadap Kerusakan Perkerasan Ruas Jalan Mr. Chr. Soplanit Kota Ambon - Suneth, Rika Abisa; Siahaya, Vera Th. C.; Kakaly, Sulastri (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
Mr. Chr. Soplanit Rumah Tiga Road Section has road damage that is quite disruptive to traffic activities due to the presence of a company that causes heavy vehicles to pass by. The activity of heavy vehicles such as trontons operated by PT. Trisamudra will pass four to five times every day at certain times ranging from 21.00 - 24.00. In addition to trontons, there are also goods trucks, pick-ups, and large trucks that pass 10-15 times to distribute Gas and other Goods. The survey conducted for 3 days of observation Monday, Wednesday and Saturday starting at 06.00 - 24.00 showed the highest volume on Saturday, namely 27,996 vehicles per day per 2 directions and the lowest volume on Wednesday, namely 24,334 vehicles. The average volume of vehicles is 26,388 vehicles per day per 2 directions. From the results of the values ​​obtained in the LHR calculation, it can be concluded that the Mr Chr Soplanit road section is included in high traffic with the number of LHRs greater than 10,000/day.